Evaluation of La-promoted Ni/Al2O3 Catalyst for Ethanol Dry Reforming - Mahadi, Bahari; Nguyen, Huu Huy Phuc; Nurul Aini, Razali; Vo, Dai-Viet N. (2015)
Greenhouse emissions from combustion of fossil fuels have led to undesirable environmental issues. Hydrogen as a clean and renewable energy is therefore demanded urgently for petroleum-based energy substitution. Although the common method for H2 production is reforming of hydrocarbons which are unsustainable, ethanol has been considered as an economically attractive feedstock for replacing hydrocarbons due to its high availability, renewability and low toxicity [1]. Ethanol steam reforming has been widely researched whilst the knowledge about dry reforming of ethanol (DRE) is still limited, especially rare-earth promoted Ni-based catalyst.